2016
DOI: 10.1590/1678-775720150353
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing orthodontic treatment time for non-surgical Class III malocclusion

Abstract: www.scielo.br/jaos http://dx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 28 publications
2
18
0
1
Order By: Relevance
“…A study by Sergl and Zentner [4] on the psychological side of the orthodontic patients found that about two-thirds were concerned about poor aesthetic. Nevertheless, the overall duration of orthodontic treatment not only worries the patients and parents, but also the orthodontists [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Sergl and Zentner [4] on the psychological side of the orthodontic patients found that about two-thirds were concerned about poor aesthetic. Nevertheless, the overall duration of orthodontic treatment not only worries the patients and parents, but also the orthodontists [5].…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of adults are undergoing orthodontic treatment and the most common concern for these patients is the treatment duration, in addition to the type of orthodontic appliance to be used in the treatment [5]. The average orthodontic treatment is from 2-3 years [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Este estudio analizo datos de ortodoncia con la poblacion objetivo (adolescentes) del Servicio Público de Salud de Chile, aunque la literaura disponible permite concluir que la edad no juega un rol critico en la duracion de los tratamientos como lo concluido por Mabreas et al (2008), Bichara et al (2016), Dyer et al (1991) y Robb et al (1998).…”
Section: Discussionunclassified
“…The impact of time on the treatment efficiency has been previously published. 24 A sample of 70 patients with Class I and Class II malocclusion treated by the same orthodontist during the same time period as the cases included in this study was considered. The aim was to determine whether or not there was a correlation between the year when treatment was started and the duration of orthodontic treatment.…”
Section: Discussionmentioning
confidence: 99%